Korea-China maritime boundary talks : implications for South China Sea - Yoon, Sukjoon (2015)
The January 2015 meeting between China and South Korea on boundary delimitation in the Yellow Sea offers a chance to improve bilateral relations and the prospect of extending agreement to other seas, in particular the South China Sea.